APPLICATION OF NANOSTRUCTURES IN MICRO- AND OPTOELECTRONIC DEVICE ENGINEERING - Eshboltayev Iqbol Mamirjonovich,; G‘ofurov Saidkamol Zokirjon ogli,; Eshboltayev Ikromjon Iqbol ogli, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper presents a scientific analysis of the application of nanostructures in the fields  of  microelectronics  and  optoelectronics.  The  operating  principles  of  modern electronic and optical devices based on nano-scale structures, their advantages, and technological  limitations  are  considered.  The  possibilities  of  enhancing  device miniaturization, speed, and energy efficiency through the use of nanostructures are discussed.